2013
DOI: 10.1111/codi.12474
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of published trials comparing the effectiveness of transanal endoscopic microsurgery and radical resection in the management of early rectal cancer

Abstract: Transanal endoscopic microsurgery appears to have clinically measurable advantages in patients with early rectal cancer. The studies included in this review do not allow firm conclusions as to whether TEMS is superior to RR in the management of early rectal cancer. Larger, better designed and executed prospective studies are needed to answer this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 54 publications
0
38
0
7
Order By: Relevance
“…A few recent systemic reviews and meta-analyses showed that for patients with T1 cancer, the distant metastasis rate and the overall survival and the disease-free survival rates did not differ between the TEM and the radical surgery groups, although the local recurrence rate after TEM was higher than that after radical surgery. The complication rate was significantly higher in the radical surgery group [2425]. …”
Section: Discussionmentioning
confidence: 99%
“…A few recent systemic reviews and meta-analyses showed that for patients with T1 cancer, the distant metastasis rate and the overall survival and the disease-free survival rates did not differ between the TEM and the radical surgery groups, although the local recurrence rate after TEM was higher than that after radical surgery. The complication rate was significantly higher in the radical surgery group [2425]. …”
Section: Discussionmentioning
confidence: 99%
“…Transanal local excision alone can cure the majority of patients with early‐stage rectal cancer, with low complication rates, good postoperative bowel function and short hospital stay. However, in all but the very earliest cancers local relapse rates are substantially higher than those after primary TME surgery. External‐beam radiotherapy is used in conjunction with TEMS to help combat the risk of occult mesorectal lymph node metastasis and to downsize the primary tumour, thereby diminishing the risk of tumour implantation during local excision.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion was disclosed as the only independent dismal prognostic factor for local failure (P = 0.04), while tumor size, ypT status, T-status downstaging, lateral/radial margins and tumor regression grade, did not reach statistical significance. Finally, a systematic review [95] comparing the effectiveness of TEM to radical surgery for T1-2 rectal tumors, concluded that the TEM procedure was associated with a higher risk of local recurrence, but was statistically equivalent to radical surgery in terms of overall mortality, overall survival and the risk of distant metastasis. We should state however, that the main bias of this review was that low risk T1, high risk T1, as well as T2 tumors, were indiscriminately enrolled.…”
Section: Long-term Results Studies On the Oncological Outcome Followimentioning
confidence: 99%